2010
DOI: 10.1097/jac.0b013e3181f53458
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Cardiac Single-Photon Emission Computed Tomography at the Primary Care Physician's Office

Abstract: Ambulatory cardiac single-photon emission computed tomography stress testing for the evaluation of coronary artery disease at the primary care physician's office is increasingly utilized without data supporting its safety. In this 2-year prospective pilot study of 1266 consecutive stress-myocardial perfusion imaging studies done in the primary care physician's office using a mobile nuclear cardiology laboratory, adverse events were mild and rare. There were no recorded events of myocardial infarction, serious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…11 Thus, assuming a baseline annual mortality of 0.5% among subjects with normal MPI, we calculated that a cohort of 1,401 subjects would be needed to attain a 75% power to detect a four-fold increase in mortality rate associated with abnormal MPI after 2 years of follow-up (2-tailed a = 0.05). We targeted recruiting 1,500 subjects to allow some room for error in our assumptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Thus, assuming a baseline annual mortality of 0.5% among subjects with normal MPI, we calculated that a cohort of 1,401 subjects would be needed to attain a 75% power to detect a four-fold increase in mortality rate associated with abnormal MPI after 2 years of follow-up (2-tailed a = 0.05). We targeted recruiting 1,500 subjects to allow some room for error in our assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] More recently, the advent of mobile, dedicated cardiac SPECT imaging instruments allowed MPI to become an ambulatory commodity available to low-volume primary care practices. 11 Although our group has shown that this practice is safe, 11 the long-term prognostic value of MPI in a primary care physician's (PCP's) office has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, upright acquisition SPECT instruments are increasing in popularity with the emergence of mobile, dedicated cardiac cameras, commonly used in the physician's office. 6,8 Upright acquisition improves patient comfort. 9 However, this technique has implications on the rates and distribution of attenuation patterns in both men and women.…”
Section: Introductionmentioning
confidence: 99%
“…Supine acquisition SPECT-MPI is associated with well recognized attenuation patterns. Nonetheless, upright acquisition SPECT instruments are increasing in popularity with the emergence of mobile cardiac-SPECT cameras, commonly used in the physician’s office [2]. While attenuation correction (AC] tools are not widely used in general [3], they are even less used with upright imaging systems.…”
Section: Introductionmentioning
confidence: 99%